Effects of omitting one udder quarter at one single milking : on milk production and SCC in mid and late lactating cows with or without re-sorting for a second milking - Nilsson, Roger (SLU/Dept. of Animal Nutrition and Management (until 231231), 2016)
The aim of this study was to investigate if one single omitted milking on one udder quarter with or without re-sorting affects milk yield and udder health in cows in mid or late lactation. The study was carried out in an automatic milking rotary (AMR). It is an identified problem in automatic milking that one or more udder quarters are incompletely milked due to failed teat cup attachment or cows kicking teatcups off. At present, cows that are registered as incompletely milked on one udder quarter or more in the AMR used in this study are resorted for a second milking since it has been shown that extended milking intervals in early- and mid-lactation can lead to a decrease in milk yield and also cause an elevated somatic cell count (SCC) which is an indicator of impaired udder health. Resorting reduces the capacity of the AMR and for the individual cow resorting leads to more time away from feed and cubicles which can impair cow welfare or milk production or both. 36 cows of Swedish Holstein and Swedish Red Breed in day 167 to 376 in lactation were used in the experiment and were divided into two groups, control and treatment. All cows were subjected to one udder quarter being omitted at one milking. After the omitted milking, control cows were resorted back for a second milking while treatment cows were directed to exit. Composite milk and udder quarter milk sampling was performed for three days before and ten days after the treatment day and used for determination of SCC, lactose, milk fat and milk protein. In addition, milk yield was registered throughout the experiment period. Milk yield was 3.7kg lower on the treatment day but no negative long-term effect on milk yield or SCC was found. Furthermore, milk yield from the omitted teat was low on resorting, indicating that a resorting likely does not lead to a complete emptying of the omitted quarter. Therefore, it was concluded that a cow in mid or late lactation has no beneficial effects of being resorted for a second milking in an AMR. A cow can instead the allowed to return to feeding and cubicles after a single incomplete milking, allowing a higher capacity of the AMR. Effects of incomplete milking in early and peak lactation and repeated incomplete milking in any stage of lactation remain to be studied.